2016
DOI: 10.1039/c6ra24064j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and solvent-free polymerisation of vinyl terephthalate for application as an anode material in organic batteries

Abstract: Solvent-free polymerisation of vinyl terephthalate was used to obtain high molecular weight polymers, whose corresponding Li-salts underlined the superiority of polymers regarding long term stability in battery tests compared to their monomeric counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…After stirring at À78 8Cf or 2.5 h, dry DMF (6.00 mL, 77.5 mmol) was slowly added, and the reaction mixture was stirred at room temperature for 2. [(1E,3Z,5Z,7Z)-Cycloocta-1,3,5,7-tetraen-1-yl]methanol (9):N aBH 4 (50.9 mg, 1.34 mmol) was added to as olution of (1E,3Z,5Z,7Z)-cycloocta-1,3,5,7-tetraene-1-carbaldehyde (350 mg, 2.69 mmol) in THF (8 mL) [(1E,3Z,5Z,7Z)-Cycloocta-1,3,5,7-tetraen-1-yl]methyl acetate (4): 4-Dimethylaminopyridine (3.2 mg, 26 mmol) and acetic anhydride (74 mL, 782 mmol) were added to as olution of [(1E,3Z,5Z,7Z)-cycloocta-1,3,5,7-tetraen-1-yl]methanol (9,1 00 mg, 745 mmol) in dry pyridine (5 mL). The reaction mixture was stirred at room temperature for 3h.H 2 O( 10 mL) was added, and the organic layer was separated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After stirring at À78 8Cf or 2.5 h, dry DMF (6.00 mL, 77.5 mmol) was slowly added, and the reaction mixture was stirred at room temperature for 2. [(1E,3Z,5Z,7Z)-Cycloocta-1,3,5,7-tetraen-1-yl]methanol (9):N aBH 4 (50.9 mg, 1.34 mmol) was added to as olution of (1E,3Z,5Z,7Z)-cycloocta-1,3,5,7-tetraene-1-carbaldehyde (350 mg, 2.69 mmol) in THF (8 mL) [(1E,3Z,5Z,7Z)-Cycloocta-1,3,5,7-tetraen-1-yl]methyl acetate (4): 4-Dimethylaminopyridine (3.2 mg, 26 mmol) and acetic anhydride (74 mL, 782 mmol) were added to as olution of [(1E,3Z,5Z,7Z)-cycloocta-1,3,5,7-tetraen-1-yl]methanol (9,1 00 mg, 745 mmol) in dry pyridine (5 mL). The reaction mixture was stirred at room temperature for 3h.H 2 O( 10 mL) was added, and the organic layer was separated.…”
Section: Methodsmentioning
confidence: 99%
“…To find suitable organic materials, new monomeric and polymeric compounds have to be identified that show highly reversible redox chemistry . While the majority of organic electrode materials developed is of p type and can be reversibly oxidized at potentials of up to 4.1 V (vs. Li/Li + ), making them suitable as battery cathode materials, fewer examples of n‐type and potential anode materials exist . These, however, are necessary to build fully organic batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility to increase the stability of redox functionalities is by incorporating them in a polymer. In this regard, polymers with pendant terephthalate groups have been synthesized and tested in lithium and sodium half‐cell experiments . Indeed, the stability of the resulting anodes is significantly improved compared to terephthalate small molecule‐based anodes.…”
Section: Electrodesmentioning
confidence: 99%
“…[18][19][20][21] While reduction of CPDs led to a fairly stable radical anion species in absence of protons (Figure 1), electro-oxidation has been shown to yield in α-pyrones. [21,22] In the course of our efforts for the development of organic molecules acting as suitable energy storage materials, [23] we got interested in CPDs as a member of the carbonyl family, which recently turned to a promising class of energy storage compounds. [24][25][26] Herein, we present the synthesis of a series of tetraaryl cyclopentadienones aiming to readdress phenyl and heterocyclic substitution effects on both available electrochemical window as well as photophysical properties.…”
Section: Introductionmentioning
confidence: 99%